2005
DOI: 10.1207/s1532799xssr0903_3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Twin Study of Early Literacy Development: Preschool and Kindergarten Phases

Abstract: Abstract. Grade 1 literacy skills of twin children in Australia (New South Wales) and the United States (Colorado) were explored in a genetically sensitive design (N = 319 pairs). Analyses indicated strong genetic influence on word and nonword identification, reading comprehension, and spelling. Rapid naming showed more modest, though reliable, genetic influence. Phonological awareness was subject to high nonshared environment and no reliable genetic effects, and individual measures of memory and learning were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
114
7
20

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(165 citation statements)
references
References 24 publications
24
114
7
20
Order By: Relevance
“…However, the importance of shared environment in the overlap among early reading skills is consistent with our own univariate examination of WRRP (Petrill et al, 2006) as well with univariate results reported by Byrne et al (2002Byrne et al ( , 2005. Moreover, these results are somewhat consistent with the typically developing sample described by Compton et al (2001).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the importance of shared environment in the overlap among early reading skills is consistent with our own univariate examination of WRRP (Petrill et al, 2006) as well with univariate results reported by Byrne et al (2002Byrne et al ( , 2005. Moreover, these results are somewhat consistent with the typically developing sample described by Compton et al (2001).…”
Section: Discussionsupporting
confidence: 91%
“…We conducted a series of Cholesky decomposition analyses (see Neale & Cardon, 1992) similar to those used in Compton et al (2001) and Byrne et al (2005). As shown in Figure 1, the covariance among phonological awareness, RAN, and outcomes (Word ID and PD, in separate analyses) was parameterized using nine latent factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, reading difficulties have been found to be more heritable in groups of children who also have deficits in phonological short-term memory (Bishop, 2001;Bishop, Adams & Norbury, 2004), suggesting that the close genetic relationship between phonology and reading extends beyond phonological awareness to the phonological system more generally. This pattern also holds longitudinally, in that the genetic factors influencing phonological awareness in preschool go on to affect children's reading a year later (Byrne et al, 2005). Less well established is the nature of the relationship between non-phonological language skills and reading.…”
Section: Speech Language and Reading: Etiology Of The Longitudinal Amentioning
confidence: 89%